Cape Espenberg Birnirk Project (CEBP) human mitogenome summary analysis (2016-2019) - O'Rourke, Dennis; Unkel, Sarah (NSF Arctic Data Center, 2020)
Genetic characterization of past Inuit populations has been limited due to the lack of genetic information from individuals associated with the Birnirk culture (1300-700 BP). “Beringian-specific” maternal lineages A2a, A2b1, and D4b1a2a1a have been documented in Thule Inuit populations (950-50 BP) throughout the North American Arctic. However, only haplotype A2a has been reported in five individuals excavated from the Paipelghak site on Chukotka peninsula. It remains unclear if Birnirk individuals are genetically distinct from Thule Inuit populations. Genetic research of past populations from western Alaska, a proposed transition area between the Birnirk and Thule material cultures, provides an opportunity to address this uncertainty. Segments from the first hypervariable region of the mitochondrial control region were sequenced from thirty-eight Birnirk individuals from the Alaskan North Slope and two Thule individuals excavated from Cape Espenberg. Twenty-three individuals yielded full, contamination-free control region sequences and possess mitochondrial lineages A2a, A2a1, A2a3, A2b1, and D4b1a2a1a. These results indicate an expansion of the observed maternal lineage diversity and confirms Birnirk populations as direct maternal ancestors to the Thule Inuit.